PUBLIC OPINION ON EFFECT OF HARASSMENT IN WORKPLACE - R, PADMESH (International Journal of Psychosocial Rehabilitation, 2020)
There are some anti-harassment policies for the companies and the HR needs to implement some policies to reduce those bullying and harassment. Harassment and bullying can cause many problems like stress, reduction in productivity, low morale, negative publicity and it would also affect the reputation of both the parties.There is no action taken against a company which has 169 sexual harassment complaint in New Delhi and a boy fronoida was barred from the company for the sexual harassment.The objective of this paper is to find an association between the workplace anti harassment and marital status. 1170 samples are collected and considered as the sample size. Dependent variables are Workplace Anti-harassment, Action towards Harassment, Effects of Harassment in the workplace. Independent sample t test, chi square and ANOVA are the research tools used in this research. The findings of the research is that age does not influence the effects of harassment in the workplace.